GRAMMATICAL LANGUAGE TRANSFER ON ENGLISH CAPTION IN INSTAGRAM’S HASHTAG #englishexpounivet - Arumi, Sihindun; Arumi, Giyatmi; Wijayava, Ratih (Surakarta English and Literature Journal, 2020)
This is such a kind of descriptive qualitative research that aims at describing the types of grammatical language transfer on English caption in instagram’s hashtag ≠englishexpounivet. Data were collected through observation and documentation by observing the English language caption of the students of a private university in Sukoharjo in their instagram’s hastag #englishexpounivet, then documenting them using screenshoot or capture (taking pictures via phone cellular). The results showed that the types of language transfer may be positive or negative. However, negative transfer was more dominant relating to grammatical field. Generally, this negative transfer did not arise alone but along with other forms. There were some cases relating to negative transfer, such as tenses, plurality, subject-verb, passive voice, preposition, pronoun, noun phrase, article, diction, capital letter, auxiliary, and translation